Redefining the Boarding School Parenting Model: Strategies for Mitigating Violence Against Students - Ratu Dian Hatifah; Alfan Huda; Nailatin Fauziyah (Universitas Darussalam Gontor, 2026)
Violence in Islamic boarding schools has become a worrying problem, with such practices seeminglytolerated because they are considered part of character building. This study uses a qualitative approach withinterview techniques, participatory observation, and document analysis. Data were analyzed using QDA Minersoftware. The study found three main findings. First, institutionalized violence continues to be practiced andlegitimized as a means of discipline. Second, there are differences in the interpretation of parenting patterns inpesantren culture. Third, restructuring parenting patterns is an important strategy for mitigating violence.These findings show the need for a renewal between old traditions that legitimize violence and moderndemands for child-friendly education. Redefining parenting is not only a matter of technical change, but alsoa transformation of values that affirms Islamic boarding schools as educational institutions oriented towardsmercy, protection, and the development of students’ potential. Thus, this study can broaden the view thata humanistic-integrative parenting model is an effective strategy in mitigating violence and is relevant fordeveloping Islamic boarding schools that are in harmony with the values of rahmatan lil-‘alamin. Keywords: Islamic Boarding School Parenting, Violence Mitigation Strategy, Students